2019
DOI: 10.1016/j.btre.2019.e00358
|View full text |Cite|
|
Sign up to set email alerts
|

Flax treatment with strategic enzyme combinations: Effect on chemical fiber composition and ease of fiber extraction

Abstract: Highlights Enzymatic treatment of flax offers a valuable alternative for dew retting. Polygalacturonase combined with xylanase activity leads to a markedly chemical refining of flax fibers. Enhanced fiber extraction efficiency reached by applying enzyme combinations. Extraction efficiencies twice as high compared to green fibers by combining polygalacturonase and pectinmethylesterase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Fiber derived from natural plants is essential for making rainforced biomaterial composites and food packaging [ 8 ]. According to recent research, enset fiber has significant chemical and physical qualities that make it a valuable raw material for packaging industries [ 18 ].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Fiber derived from natural plants is essential for making rainforced biomaterial composites and food packaging [ 8 ]. According to recent research, enset fiber has significant chemical and physical qualities that make it a valuable raw material for packaging industries [ 18 ].…”
Section: Background Of the Studymentioning
confidence: 99%
“…In contrast, the presence of only endo 1, 4-β-xylanase in Feedlyve was not able to induce substantial modifications of the flax properties. De Prez et al [25,35] investigated different enzyme combinations based on several pectinase and hemicellulase activities, including up to three different enzymes applied to flax fibres, and discussed their effects on the chemical fibre composition, ease of fibre extraction and fibre fineness.…”
Section: Characterization Of Flax Yarns After Enzymatic Treatmentmentioning
confidence: 99%
“…In particular, the use of enzymes for textile and natural fibre modification is swiftly growing. The enzymatic treatment represents a green way to modify natural fibres, and in literature enzymatic treatments have been used with two final aims: (i) the extraction of bast fibres from non-fibrous tissues in stems as an alternative to dew retting [24,25], and (ii) the surface modification of fibres already extracted in order to reduce hydrophilicity and increase thermal stability [21,26]. In these latter studies, the enzymatic treatment was reported to be able to remove undesirable substances like pectin, hemicelluloses, lignin and waxes from the surface of the fibres, improving fibre/matrix adhesion, moisture resistance and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers (hemp, jute, flax and kenaf) and glass fibers have comparable specific mechanical properties. [4][5][6] Furthermore, natural fibers are abundant, renewable, biodegradable and cheap. In addition, they are harmless and do not damage the processing equipment in contrast to glass fibers.…”
Section: Introductionmentioning
confidence: 99%